(untitled) (JOURNAL OF ADVANCES IN BIOLOGY, 2017)
The demographic development, the trade exchanges as well as the increasing human needs represent a major threat to biodiversity. These phenomena caused the extinction of a large number of plant species creating ecological conditions favourable to the appearance of new species harmful to the native ones. In fact, the lands and forests of the Lesser Antilles have gradually been damaged, resulting in regressive forests. In Martinique, the forests undergo a significant degree of anthropization facilitating the installation of invasive species. Triphasia trifolia is one of these invasive species. Introduced from Southeast Asia as an ornamental plant, the species has become naturalized and colonizes the coastal areas to the detriment of indigenous populations. Inventories in the xeric south of Martinique (the commune of Vauclin), allowed us to decipher the main life characteristics of Triphasia trifolia.